The subjectivity of dictionary readers: the case of the OED - Ogilvie, S (2010)
From the earliest days of the OED, members of the public have read texts and sent quotations to the editors. These quotations formed the foundation of each dictionary entry, showing how, when, and where a word was used over time. In 1879, James Murray provided guidelines for these readers, but the choice of word and citation rested with the readers, not the editors. This process was far from straight forward, especially for vocabulary considered marginal, such as slang or foreign words. Using letters and documents from the OED archives, this paper compares the work of two nineteenth-century readers, assessing in particular the foreign words they chose to highlight and send to the editors, and, more importantly, those which they chose to ignore. It traces the implications that these choices had on the final dictionary text, and ultimately on the bounds of the English language. Today, in addition to the predominant use of electronic resources to gather quotations, OED editors still rely on the work of dictionary readers, and the actual reading process remains unchanged since Murrayʼs day. This paper asks whether dictionary readers still have a place in the dictionary-making process, and considers what new roles they might play in the future.